Proteomic Analysis of Two Weight Classes of Mule Duck “foie gras” at the End of an Overfeeding Period - Lo, Bara; Marty-Gasset, Nathalie; Pichereaux, Carole; Bravo, Céline; Manse, Hélène; Domitile, Renaud; Rémignon, Hervé (Frontiers in Physiology, 2020)
The weight of the liver is one of the important selection criteria in the quality of foie gras. This factor is highly variable despite the fact that individuals are reared, force-fed and slaughtered in the same way. In this study, we performed an analysis of the proteome profile of two weight classes of light (between 550 g and 599 g) and heavy (more than 700 g) livers. For the analysis of the proteic extracts, a liquid chromatographic analysis coupled with mass spectrometry was carried out. In livers with low weights, aerobic energy metabolism, proteins anabolism and lipids metabolism oriented towards export and beta-oxidation were overexpressed. On the contrary, high weight livers were characterized by anaerobic energy metabolism and a more active proteins catabolism associated with cell death by apoptosis and reorganisation of the cell structure.